DCZ3112, a novel Hsp90 inhibitor, exerts potent antitumor activity against HER2-positive breast cancer through disruption of Hsp90-Cdc37 interaction. (10th October 2018) - Chen, Xiangling; Liu, Peng; Wang, Quanren; Li, Yun; Fu, Li; Fu, Haoyu; Zhu, Jianming; Chen, Zhaoqiang; Zhu, Weiliang; Xie, Chengying; Lou, Liguang
Abstract: Hsp90 regulates the stability of oncoproteins important in tumor development and progression, and represents a potential therapeutic target. However, all Hsp90 inhibitors currently in clinical trials target Hsp90 ATPase activity and exhibit low selectivity and high toxicity. In this study, we discovered a new Hsp90 inhibitor, DCZ3112, with a novel mechanism of action. DCZ3112 directly bound to the N-terminal domain of Hsp90 and inhibited Hsp90-Cdc37 interaction without inhibiting ATPase activity. DCZ3112 inhibited the proliferation predominantly in HER2-positive breast cancer cells, including those resistant to the classical Hsp90 inhibitor geldanamycin, which mainly targets ATPase. DCZ3112 produced synergistic in vitro activity in inhibiting cell proliferation, inducing G1 -phase arrest and apoptosis, and reducing AKT and ERK phosphorylation. Consistent with this, DCZ3112 alone inhibited the growth of HER2-positive BT-474 xenografts, and exhibited enhanced antitumor activity when combined with the anti-HER2 antibody trastuzumab. Importantly, DCZ3112 also significantly inhibited the growth of trastuzumab-resistant BT-474 cells, and combined treatment retained synergistic antitumor activity. Thus, our findings show that disrupting Hsp90-Cdc37 interaction may represent a promising strategy against HER2-positive breast cancer, especially those with acquired resistance to trastuzumab. Highlights: DCZ3112 is a novel Hsp90 inhibitor that disrupts Hsp90-Cdc37 interaction. DCZ3112 overcomes resistance to traditional Hsp90 inhibitors. DCZ3112 predominantly acts in HER2-positive breast cancer. The combination of DCZ3112 and anti-HER2 antibodies exerts synergistic effects in breast cancer. DCZ3112 alone or with anti-HER2 antibodies overcomes trastuzumab resistance.